MODERN APPROACHES TO TEACHING HISTORY - Jurabek Begaliev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Historical memory has been at the center of attention throughout human history. In this article analyzes the developmental characteristics of history teaching methods in line with human development on the basis of local and foreign sources..